ASEAN PRINCIPLE: DILEMMA AND NECESSITY - Arindra Ahmad Fauzan (WANUA : Jurnal Hubungan Internasional, 2017)
The purpose of this study is to explain how ASEAN solved problems in stabilizing their territory. As we know the formation of ASEAN as a regional organization of Southeast Asia is to liberate countries in Southeast Asia from the influence of The Great Powers. This is in line with the realism that deeply bound within ASEAN. Ahead of the 15th anniversary of the formation of ASEAN, there was a major conflict between Vietnam and Cambodia, precisely in the 1970s. This is one of the catalysts that destabilize the ASEAN’s stances to avoid various types of multilateral relations. The method used in this research is qualitative with historical analysis from various literatures. After successfully resolving the conflict, in 1994 ASEAN established ARF as a workplace to discuss security in Asia, in order to facilitate such conflicts to occur again. ARF members are not only ASEAN countries but also superpowers. This is contrary to the foundation of ASEAN itself. In essence it shows that realism is willing to subdue with liberalism.